Odpowiedzi

2009-11-25T19:18:17+01:00
2a+2(-3b+a)-6 dla a= 1 i b =-0,5
2a+2(-3b+a)-6= 2*1+2(-3*(-0,5)+1)-6= 2+2(-0,5)-6= 2-1-6= -5
b)5x-4y(-6x+12)-(-5)y dla x= 6 i y=-6
5x-4y(-6x+12)-(-5)y= -30+24(-30+12)+30= 24* (-18) = 432
c)7+(-3)(x-2y)-1\2(-4y+x) dla x=-0,4 i y=1,2
7+(-3)(x-2y)-1\2(-4y+x)= 7+ (-3)(-0,4-2,4)-1/2(-4,8-0,4)= 7+(-3)*(-2,8)-1/2(-5,2)= 7+8,4+2,6=18
1 5 1
2009-11-25T19:27:57+01:00
A) 1/2a-6b+2a-6=1/2+3+2-6=5,5-6= -0,5
b) 5x+24xy-48y+5y=5x-43y+24xy=30+258+24*6*(-6)=288-864= -576
c) 7-3x+6y+2y-1/2x=7-3,5x+8y=7+1,4+9,6= 18